Harmonisasi Antar Umat Beragama Dalam Negara Multi Agama Dalam Perspektif Al-Quran - Abdul Muqit (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Intolerance in the name of religion is still common in this country. Excessive religious fanaticism and lack of religious knowledge are among the contributing factors. Likewise, politics wrapped in religion is still often done by some politicians, which in turn causes rifts between nations. Therefore this article will discuss the harmonization of religious communities in multi-religious and ethnic countries from the perspective of the Koran by using interdisciplinary thematic interpretation methods. The results of the study concluded that the differences in religion and ethnicity were sunnatullah. In building harmony among religious communities, the Koran encourages fair and good relations between religious communities, makes friends, does not berate each other, does not impose certain religions, carries out the teachings of each other's religion and does not interfere with other people's religions.